Successful use of Solumbra technique in renal artery thrombectomy: A case report - Long Nguyen Tuan, MD; Hung Nguyen Duc, MD; Lam Truong Hoai, MD; Minh Tran Duc, MD; Vu Nguyen Hoai, MD (Radiology Case Reports)
Acute renal infarction is a condition where the blood supply to the kidney is suddenly blocked, leading to tissue damage and potential loss of kidney function. If the patient is not treated promptly, it can lead to severe complications such as permanent kidney damage, acute kidney failure, hypertension and chronic kidney disease. A 52-year-old male patient was admitted to the emergency department with persistent left flank pain within 21 h after onset. A CT scan with contrast of the abdomen showed a renal infarction in the left kidney caused by a clot in the anterior branch of the left renal artery. The patient underwent a thrombectomy and revascularization using the Solumbra technique. After the intervention, the patient's symptoms significantly improved, and their renal function recovered within 1 month. This result indicates the effectiveness of the Solumbra technique in restoring blood flow in an occluded renal artery, highlighting its potential in managing complex vascular conditions.